2021
DOI: 10.3389/fcomm.2020.611935
|View full text |Cite
|
Sign up to set email alerts
|

Reading Fictional Narratives to Improve Social and Moral Cognition: The Influence of Narrative Perspective, Transportation, and Identification

Abstract: There is a long tradition in philosophy and literary criticism of belief in the social and moral benefits of exposure to fiction, and recent empirical work has examined some of these claims. However, little of this research has addressed the textual features responsible for the hypothesized cognitive effects. We present two experiments examining whether readers’ social and moral cognition are influenced by the perspective from which a narrative is told (voice and focalization), and whether potential effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Hence, markers of narrative viewpoint might be an interesting candidate in the search for textual determinants of the social-cognitive potential of narratives (see also Koopman and Hakemulder, 2015). Note that a recent study did not find a difference in the effect of a single exposure to a narrative with or without direct access to the inner worlds of protagonists on social-cognitive abilities (internal vs. external focalization; Wimmer et al, 2021). By contrast, reasoning from the present findings, it may be hypothesized that a study that combines such a textual approach with the individual differences approach outlined here, might reveal interesting patterns of results.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Hence, markers of narrative viewpoint might be an interesting candidate in the search for textual determinants of the social-cognitive potential of narratives (see also Koopman and Hakemulder, 2015). Note that a recent study did not find a difference in the effect of a single exposure to a narrative with or without direct access to the inner worlds of protagonists on social-cognitive abilities (internal vs. external focalization; Wimmer et al, 2021). By contrast, reasoning from the present findings, it may be hypothesized that a study that combines such a textual approach with the individual differences approach outlined here, might reveal interesting patterns of results.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…However, two central issues remain unresolved. The first is the robustness of these findings in view of multiple failed replications and studies with null results (see, e.g., Chlebuch et al, 2020;Samur et al, 2018;Wimmer, Currie, et al, 2021, 2022. Second, a capacity for high levels of empathy and ToM is generally considered desirable (e.g., A. M. Ferguson et al, 2021;Goldstein & Winner, 2012) and research confirming that reading fiction has robust positive effects on these capacities is likely to be welcomed.…”
Section: Empathy and Theory Of Mind (Tom)mentioning
confidence: 95%
“…First, it is often suggested that written fiction is a source of knowledge in the sense that it enables readers of all ages to acquire correct information and desirable attitudes (Best, 2021). Note, however, that a study by Wimmer, Currie, et al (2021) found that frequent readers of fiction and frequent readers of nonfiction demonstrate equally high levels of general knowledge. Similarly, Hopkins and Weisberg (2017), in their review, state that "the current body of evidence does not allow us to conclude definitively whether learning from fiction is the same, better, or worse than learning from other sources" (p. 62).…”
Section: Knowledge Biases and Prejudicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidd & Castano, 2013, 2019; Kidd, Ongis, & Castano, 2016; Panero et al, 2016; Samur, Tops, & Koole, 2018) as such false alarms can reflect a rather inattentive participation style. Excluding participants with more than two guesses is more rigorous than measures applied in previous experiments (e.g., Kidd & Castano, 2019) since Moore and Gordon (2015) suggested a higher penalty for selecting mock authors than originally recommended (for an example applying this more stringent cut-off score see Wimmer, Friend, Currie, & Ferguson, 2021). In these exploratory analyses, all significant effects remained as in the analyses reported above.…”
Section: Exploratory Analysesmentioning
confidence: 99%